System and method for extracting high-purity potassium salt using cement by-pass dust

The multi-module collaborative processing system solves the problems of low potassium salt leaching rate and high separation difficulty in cement kiln bypass ash, realizes the efficient extraction and resource utilization of high-purity potassium salt, and improves the operating efficiency of cement kiln system and clinker quality.

CN120393855BActive Publication Date: 2026-02-03TIANNENG CEMENT CO LTD +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510553778.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-02-03
Estimated Expiration
2045-04-29

AI Technical Summary

Technical Problem

In existing technologies, the chlorine and potassium content of cement kiln bypass ash is high, the particle size is fine, and the density is light, which makes it difficult to dispose of safely, affects the operating efficiency of the cement kiln system and the quality of clinker, and the potassium salt leaching rate is low, separation is difficult, and the purity is poor.

Method used

A multi-module collaborative processing system is adopted, including a magnetic separation module, a dynamic activation module, a countercurrent leaching module, an ion sieving module, and a crystal phase control module. Through gradient magnetic separation, NH4Cl-assisted calcination, hydrochloric acid-ammonium fluoride synergistic leaching, bipolar membrane electrodialysis, and ultrasonic crystallization, high-purity potassium salts are efficiently extracted.

Benefits of technology

This achievement represents a breakthrough in both potassium salt extraction rate and purity, reduces overall costs, provides efficient potassium salt extraction and resource utilization, and improves the operating efficiency of cement kiln systems and clinker quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120393855B_ABST
    Figure CN120393855B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of industrial solid waste resource utilization, and particularly relates to a system for extracting high-purity potassium salt by using cement bypass ash, which comprises: a magnetic separation module for separating Fe3O4 magnetic phase in the bypass ash under a 0.8-1.2T gradient magnetic field, a dynamic activation module for two-stage calcination under the assistance of NH4Cl, a countercurrent leaching module for realizing hydrochloric acid-ammonium fluoride synergistic leaching under the condition of pH 0.5-2.5 through a three-stage series reactor, an ion sieve separation module comprising a bipolar membrane electrodialysis unit and a Li + type K-LTL molecular sieve adsorption tower, and a crystal phase regulation module for preparing potassium salt crystals with Cl ‑ content ≤0.1% by using real-time feedback of super-saturation through conductivity; and a cyclic regeneration module. After purification, the potassium salt in the present application can be directly packaged and sold in the market, and the remaining bypass ash can continue to be reused to produce cement, and the comprehensive cost is reduced by more than 35% compared with the traditional process, thereby providing an integrated solution of “efficient potassium extraction-high-purity separation-zero waste recycling” for the solid waste of the cement industry.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of industrial solid waste resource utilization, and particularly relates to a system and method for extracting high-purity potassium salt by using cement bypass ash. BACKGROUND

[0002] In the production of cement enterprises, low-quality cement production raw materials, fuels, and solid wastes are fully utilized to replace high-quality raw materials and coal, and the mining is gradually reduced. However, the poor quality of raw materials and fuels has a certain impact on the normal operation of the cement kiln, especially the raw materials and fuels with high content of chlorine, alkali and sulfur, such as household garbage, incineration bypass ash and rectification residue, which enter the cement kiln and cause the system to be rich in chlorine elements, resulting in skinning and blocking of the cement kiln system, thereby affecting the normal operation of the system and the quality of the clinker. In order to improve the operation efficiency of the cement kiln system and solve the problem of the circulation of volatile substances such as chlorine, potassium, sodium and sulfur in the cement kiln, the cement kiln is provided with a bypass air release facility to discharge the bypass ash in the form of bypass ash from the cement kiln system.

[0003] The bypass air release is to extract part of the gas from the enrichment point of harmful elements in the cement kiln, thereby destroying the circulation of chlorine elements in the system and reducing the risk of skinning in the system, which can effectively improve the operation rate of the kiln system. Therefore, for the cement plant that cooperatively disposes high-chlorine waste, the bypass air release system is a very important supporting facility. At present, many cement plants that cooperatively dispose solid waste in China have set up a bypass air release system. The bypass air release system can effectively reduce the problem of aluminum element circulation enrichment in the cement kiln system. However, the bypass ash collected by the bypass air release system has the characteristics of high chlorine content, high potassium content, fine particle size and light density, and the safe disposal of the bypass ash has become a new problem that limits the use rate of "alternative fuel" in the cement kiln.

[0004] The invention patent with application number 201510804238.4 discloses a method for utilizing the dust collection ash of the bypass air release of the rotary kiln, which belongs to the technical field of industrial solid waste resource treatment and also belongs to the technical field of potassium salt production. The method is to mix and stir the dust collection ash of the bypass air release of the rotary kiln with 60-95℃ primary industrial water under the condition that the solid-liquid mass ratio is 1 / 2-1 / 5, and then to separate the solid and the liquid. The dust collection ash after the solid-liquid separation is dried and crushed and then returned to the cement production system. The solution after the solid-liquid separation is evaporated and concentrated, decalcified, adjusted in pH value, and separated by filter membrane to produce potassium chloride and potassium sulfate products by crystallization, and to produce a by-product of precipitated calcium carbonate.

[0005] There are still problems such as low leaching rate, difficulty in separation, and poor crystallization purity in the prior art. SUMMARY

[0006] The present application provides a system and method for extracting high-purity potassium salt by using cement bypass ash, which can solve the problem of low leaching rate of potassium salt.

[0007] To solve the above technical problems, the application provides the following technical solutions: 1. A system for extracting high-purity potassium salt using cement bypass ash, comprising:

[0008] Magnetic separation module: used for separating Fe3O4 magnetic phase in the bypass ash under a 0.8-1.2T gradient magnetic field, so that the Fe2O3 content is reduced to ≤1.5wt%;

[0009] Dynamic activation module: used for two-stage calcination with the assistance of NH4Cl, so that the potassium feldspar decomposition rate is ≥85%, and activated ash with a specific surface area of ≥18m 2 / g is generated;

[0010] Countercurrent leaching module: used for realizing hydrochloric acid-ammonium fluoride synergistic leaching under the condition of pH 0.5-2.5 through a three-stage series reactor;

[0011] Ion sieve separation module: including a bipolar membrane electrodialysis unit and a Li + type K-LTL molecular sieve adsorption tower, and selectively separating K + / Na + to 50:1 or more;

[0012] Crystal phase regulation module: used for preparing potassium salt crystals with a Cl - content of ≤0.1% by means of real-time feedback of super-saturation through conductivity, in combination with 28kHz pulse ultrasonic waves and KCl crystal seeds with preferred orientation of crystal faces;

[0013] Cyclic regeneration module: used for returning the leaching residue to a cement kiln after mixing with 3wt% CaF2, and electrolyzing the tail gas absorption liquid to generate sodium hypochlorite.

[0014] The basic principle and beneficial effects of the scheme are as follows:

[0015] The application provides a cement bypass ash high-value utilization system and method based on multi-module cooperation, which realizes the accurate removal of Fe3O4 (Fe2O3≤1.5wt%), NH4Cl-assisted two-stage calcination activation (potassium feldspar decomposition rate ≥85%), hydrochloric acid-ammonium fluoride synergistic countercurrent leaching (potassium leaching rate ≥92%), bipolar membrane-molecular sieve combined ion sieve separation (K + / Na + separation ratio ≥50:1), ultrasonic wave-crystal seed coupled crystallization regulation (Cl - ≤0.1%), and full-process recycling of by-products (leaching residue activity index ≥80%, mother liquor reuse ≥5 times), so that the potassium salt extraction rate, purity (≥99.3%) and resource utilization rate are simultaneously broken through, the comprehensive cost is reduced by more than 35% compared with the traditional process, and an integrated solution of “efficient potassium extraction-high-purity separation-zero waste recycling” is provided for the solid waste of the cement industry.

[0016] Further, the magnetic field strength of the magnetic separation module is set in three sections of gradient as 0.8T, 1.0T and 1.2T;

[0017] The calcination product of the dynamic activation module is detected by XRD, showing that the intensity of the characteristic peak 2θ of kalsilite at 28.5° is reduced by 82-87%, and the characteristic peak 2θ of the newly formed KCl at 31.3° has a half peak width ≤0.18°.

[0018] Further, the countercurrent leaching module comprises:

[0019] The first leaching unit: reaction temperature 80-90℃, liquid-solid ratio 8:1, ultrasonic assistance;

[0020] The secondary strengthening unit: adding 0.05-0.1wt% sodium dodecyl sulfonate as an interfacial active agent;

[0021] The third washing unit: the washing water is recycled to the preparation of the first leaching agent.

[0022] Further, the ion sieve separation module:

[0023] The bipolar membrane electrodialysis unit synchronously generates 0.5-1.0mol / L NaOH solution, which is used for pH adjustment;

[0024] Li + The adsorption capacity of K-LTL molecular sieve of type K-LTL for Na + is ≥2.5mmol / g, and the regeneration efficiency is ≥95%.

[0025] Further, the crystal phase regulation module:

[0026] The supersaturation is calculated in real time by a conductivity-concentration calibration curve, with a control accuracy of ±5%;

[0027] The crystal seed addition amount is 0.1-0.5% of the solution mass, and the crystal roundness is ≥0.85.

[0028] A method for extracting high-purity potassium salt by using cement bypass ash, comprising the following steps:

[0029] Step 1: magnetic separation-activation pretreatment: separate Fe3O4 in the bypass ash in a 0.8-1.2T gradient magnetic field, and reduce the Fe2O3 content to ≤1.5wt%;

[0030] Mix the magnetic separation ash with 1.5wt% NH4Cl, and under the conditions of O2 concentration 30%, flow rate 5L / min:

[0031] First stage: calcine at 600℃ for 30 minutes, and the kalsilite is decomposed into KCl and Al2O3;

[0032] The second stage involves calcining at 400℃ with CO2 for 60 minutes to generate surface carbonate active sites.

[0033] Step 2: Three-stage countercurrent leaching

[0034] Primary leaching: Leaching with 4 mol / L hydrochloric acid at 80℃ using ultrasonic leaching (40 kHz, 0.5 W / cm²). 3 40 minutes;

[0035] Secondary enhancement: Add 0.1 mol / L ammonium fluoride and 0.1 wt% sodium dodecyl sulfonate, and continue leaching for 20 minutes;

[0036] Three-stage washing: Rinse the leachate residue with pure water in a counter-current manner, and reuse the washing liquid for the first-stage leaching;

[0037] Step 3: Ion-targeted purification

[0038] Add 5-10 g / L sodium thiosulfate to the leachate to precipitate heavy metal ions Cu. 2+ Pb 2+ ;

[0039] ≥90% Na was removed by bipolar membrane electrodialysis. + ;

[0040] Using Li + Type K-LTL molecular sieve adsorbs residual Na + After adsorption, K + Purity ≥ 99.3%;

[0041] Step 4: Dynamic Crystallization Control

[0042] Concentrate the purified solution to a potassium ion concentration of 150±5 g / L and a supersaturation of 130% and then add KCl seed crystals.

[0043] Cool down to 30℃ at a rate of 1℃ / min, start a temperature oscillation program of ±5℃ / 10min, and simultaneously apply 28kHz ultrasound.

[0044] Step 5: Closed-loop recycling

[0045] The leaching residue, after being mixed with 3wt% CaF2 and returned to the cement kiln, showed an activity index ≥80% after 28 days.

[0046] The crystallization mother liquor is recycled 5-8 times via nanofiltration membrane;

[0047] The exhaust gas absorbent is electrolyzed to generate sodium hypochlorite with an effective chlorine content of ≥5%.

[0048] Furthermore, the BET specific surface area of ​​the activated ash from step 1 reaches 18-22 m². 2 / g, potassium element solubility ≥90%;

[0049] The residual K2O content in the leaching residue from step 2 is ≤0.5wt%.

[0050] Furthermore, in step 3: Na+ from bipolar membrane electrodialysis + Migration rate ≥ 0.15 mol / (m 2 ·h);

[0051] The operating space velocity of the molecular sieve adsorption tower is 2-4 h⁻¹. -1 Na + Penetration capacity ≥2.2mmol / g.

[0052] Furthermore, in step 4: the seed crystal particle size is 50-80 μm, and the addition amount is 0.3 wt%.

[0053] Final crystal Cl - Content ≤0.08%, particle size distribution span (D90-D10) / D50 ≤0.7.

[0054] Furthermore, in step 5: the nanofiltration membrane has an organic matter rejection rate of ≥95%; the current efficiency of sodium hypochlorite electrolysis is ≥85%. Furthermore, in step 1, the bypass ash is pretreated with microwaves before magnetic separation for 5-15 minutes. Attached Figure Description

[0055] Figure 1 This is a flowchart illustrating the steps of a method for extracting high-purity potassium salts using cement bypass ash. Detailed Implementation

[0056] The following detailed description illustrates the specific implementation method:

[0057] Example 1 is attached. Figure 1 As shown,

[0058] A system for extracting high-purity potassium salts using cement bypass ash, characterized in that it comprises:

[0059] Magnetic separation module: Used to separate the Fe3O4 magnetic phase in bypass ash under a gradient magnetic field of 0.8-1.2T, reducing the Fe2O3 content to ≤1.5wt%. Based on the strong magnetism of Fe3O4 (saturation magnetization ≥90 emu / g), the gradient magnetic field (0.8-1.2T) achieves physical separation of the magnetic and non-magnetic phases. The gradient magnetic field design progressively increases the magnetic field strength (0.8T→1.0T→1.2T), achieving a Fe3O4 removal rate ≥90%. XRD analysis of the calcination products from the dynamic activation module shows an 82-87% reduction in the intensity of the characteristic peak of potassium nepheline (2θ=28.5°), and a half-peak width of the characteristic peak of newly formed KCl (2θ=31.3°) ≤0.18°. This selectively captures Fe3O4 particles of different sizes, avoiding the residue of weakly magnetic impurities caused by a single magnetic field strength. After magnetic separation, the Fe2O3 content is reduced to ≤1.5wt%, which reduces the inhibitory effect of iron impurities on the subsequent acid leaching reaction, while retaining the chemical activity of potassium.

[0060] Dynamic activation module: Used for two-stage calcination with NH4Cl assistance (first stage calcination at 600℃ for 30 minutes, second stage calcination at 400℃ with CO2 flow rate 2L / min), to achieve a potassium nepheline decomposition rate ≥85% and generate a specific surface area ≥18m². 2 / g of activated ash; chemical dissociation and surface activation of potassium nepheline (KAlSiO4) are achieved through two-stage calcination assisted by NH4Cl.

[0061] The first stage (600℃): NH4Cl thermally decomposes to generate HCl gas (NH4Cl→NH3↑+HCl↑), and HCl reacts with potassium nepheline to generate soluble KCl (KAlSiO4+4HCl→KCl+AlCl3+SiO2+2H2O), which destroys the aluminosilicate crystal lattice structure.

[0062] Second stage (400℃ CO2): CO2 reacts with hydroxyl groups (-OH) on the surface of activated ash to form carbonate active sites (-OH + CO2 → -OCOO). - +H + This enhances the interfacial mass transfer efficiency of subsequent leaching reactions.

[0063] Effects: Potassium nepheline decomposition rate ≥85%, specific surface area ≥18m² 2 / g, potassium leaching activity is increased by 2-3 times.

[0064] Countercurrent leaching module: used to achieve a potassium leaching rate ≥92% through a three-stage series reactor (first stage 3-5 mol / L hydrochloric acid, second stage 1-2 mol / L hydrochloric acid + 0.1-0.3 mol / L ammonium fluoride, third stage countercurrent washing) under pH 0.5-2.5 conditions; the countercurrent leaching module includes:

[0065] Primary leaching unit: reaction temperature 80-90℃, liquid-to-solid ratio 8:1, ultrasonic assistance (40kHz, 0.3-0.5W / cm²). 3 );

[0066] Secondary reinforcement unit: Add 0.05-0.1wt% sodium dodecyl sulfate as a surfactant;

[0067] Three-stage washing unit: Washing water is circulated to the first-stage leaching agent preparation, increasing potassium recovery rate by 15-20%.

[0068] The synergistic dissolution mechanism of hydrochloric acid-ammonium fluoride composite leaching agent is adopted.

[0069] Hydrochloric acid function: H + Attacking the aluminosilicate network releases encapsulated potassium (KAlSiO4+4H) + →K + +Al 3+ +SiO2+2H2O).

[0070] Ammonium fluoride function: F - It reacts with SiO2 to form soluble [SiF6]. 2- (SiO2+6F - +4H + →[SiF6] 2- +2H2O) breaks the silica gel coating and releases residual potassium.

[0071] Process optimization: Three-stage countercurrent leaching uses liquid-solid countercurrent contact (liquid-solid ratio 8:1) combined with ultrasonic cavitation effect (40kHz) to enhance mass transfer, resulting in a potassium leaching rate of ≥92%.

[0072] Ion sieving module: includes a bipolar membrane electrodialysis unit (15-25V operating voltage) and Li + A K-LTL molecular sieve adsorption tower (operating temperature 60℃) is configured for the selective separation of K... + / Na + Up to 50:1 or higher; the ion sieving module:

[0073] The bipolar membrane electrodialysis unit simultaneously generates 0.5-1.0 mol / L NaOH solution, which is recycled for pH adjustment;

[0074] Li + Type K-LTL molecular sieve for Na + The adsorption capacity is ≥2.5 mmol / g, and the regeneration efficiency is ≥95%. This is based on the ion-selective separation mechanism of bipolar membrane electrodialysis and molecular sieves.

[0075] Bipolar membrane electrodialysis: Under the drive of an electric field (15-25V), Na... + Because the migration rate is faster than K+ It preferentially passes through the cation exchange membrane into the cathode chamber, simultaneously generating NaOH solution (H2O→H). + +OH - Na + +OH - →NaOH).

[0076] Li + Type K-LTL molecular sieve: molecular sieve pore size (0.71 nm) and Li + Ionic radius matching (0.076 nm) allows for selective adsorption of Na through ion sieving effect. + (Na + Radius 0.095nm > Li + ), and K + (Radius 0.138nm) Due to its excessive size, it cannot enter the channel, thus failing to achieve K... + / Na + Separation ratio ≥ 50:1.

[0077] Crystal phase control module: Used to provide real-time feedback of supersaturation (120-150%) via conductivity, combined with 28kHz pulsed ultrasound (power density 0.2-0.5W / cm²). 3 KCl seed crystals with preferred orientations of (200) and (200) crystal planes were used to prepare Cl - Potassium salt crystals with a content ≤0.1% and a D50 of 80-120 μm; directional crystal growth based on crystallization kinetics and interfacial energy regulation.

[0078] Supersaturation feedback: Real-time monitoring of solution supersaturation (120-150%) via conductivity-concentration calibration curve to precisely control the crystal nucleation rate.

[0079] Ultrasound intervention: 28kHz pulsed ultrasound (0.2-0.5W / cm) 3 This generates cavitation, breaks up crystal nuclei aggregates, and inhibits secondary nucleation.

[0080] Seed induction: KCl seed crystals with preferred orientation on the (200) crystal plane were added, and KCl seed crystals were guided by lattice matching. + Directional deposition reduces Cl - Impurity embedding, crystal Cl - Content ≤0.1%.

[0081] The crystal phase control module:

[0082] Supersaturation is calculated in real time using a conductivity-concentration calibration curve, with a control accuracy of ±5%.

[0083] The amount of seed crystals added is 0.1-0.5% of the solution mass, and the crystal roundness is ≥0.85 (detected by Malvern particle size analyzer).

[0084] Recycling module: Used to return leaching residue to the cement kiln after adding 3wt% CaF2; to recycle the crystallization mother liquor ≥5 times via nanofiltration membrane (molecular weight cutoff ≥200Da); and to generate sodium hypochlorite by electrolysis of the tail gas absorbent. Design of a complete resource utilization pathway for byproducts.

[0085] Leaching residue: 3wt% CaF2 is added as a mineralizer to promote the mineralization of CaO and CO2 in the leaching residue to form CaCO3 (CaO+CO2→CaCO3), thereby enhancing its activity as a cement admixture (28-day activity index ≥80%).

[0086] Crystallization mother liquor: Organic matter and colloidal impurities are removed by nanofiltration membrane (molecular weight cutoff ≥200Da). The mother liquor is recycled ≥5 times, and the potassium recovery rate is maintained at ≥90%.

[0087] Tail gas absorbent: Electrolyzed Cl-containing - The absorbent (NaCl) produces sodium hypochlorite (2NaCl + 2H₂O → ClO₂). - +H2↑+2NaOH), with an effective chlorine concentration ≥5%, achieving resource utilization of waste gas.

[0088] It also relates to a method for extracting high-purity potassium salts using cement bypass ash, including the following steps:

[0089] Step 1: Magnetic separation-activation pretreatment: The bypass ash is placed in a gradient magnetic field of 0.8-1.2T to separate Fe3O4, and the Fe2O3 content is reduced to ≤1.5wt%.

[0090] The magnetic separation ash was mixed with 1.5 wt% NH4Cl under the conditions of 30% O2 concentration and a flow rate of 5 L / min:

[0091] In the first stage, the potassium nepheline was calcined at 600℃ for 30 minutes, during which potassium nepheline decomposed into KCl and Al2O3.

[0092] In the second stage, CO2 is introduced at 400℃ and calcined for 60 minutes to generate surface carbonate active sites; the BET specific surface area of ​​the activated ash from step 1 reaches 18-22 m². 2 / g, potassium element solubility ≥90% (ICP-OES detection);

[0093] Step 2: Three-stage countercurrent leaching

[0094] Primary leaching: Leaching with 4 mol / L hydrochloric acid at 80℃ using ultrasonic leaching (40 kHz, 0.5 W / cm²). 3 40 minutes;

[0095] Secondary enhancement: Add 0.1 mol / L ammonium fluoride and 0.1 wt% sodium dodecyl sulfonate, and continue leaching for 20 minutes;

[0096] Three-stage washing: Rinse the leaching residue with pure water countercurrently, and reuse the washing liquid for the first-stage leaching; the residual K2O content in the leaching residue of step 2 is ≤0.5wt% (XRF detection).

[0097] Step 3: Ion-targeted purification

[0098] Add 5-10 g / L sodium thiosulfate to the leachate to precipitate heavy metal ions (Cu). 2+ Pb 2+ );

[0099] ≥90% Na was removed by bipolar membrane electrodialysis (20V voltage). + ;

[0100] Using Li + Type K-LTL molecular sieve adsorbs residual Na + After adsorption, K + Purity ≥ 99.3%; In step 3:

[0101] Na+ in bipolar membrane electrodialysis + Migration rate ≥ 0.15 mol / (m 2 ·h);

[0102] The operating space velocity of the molecular sieve adsorption tower is 2-4 h⁻¹. -1 Na + Penetration capacity ≥2.2mmol / g.

[0103] Step 4: Dynamic Crystallization Control

[0104] When the purified solution is concentrated to a potassium ion concentration of 150±5g / L and the supersaturation reaches 130%, KCl seed crystals with (200) crystal faces are added.

[0105] Cool down to 30℃ at a rate of 1℃ / min, start a temperature oscillation program of ±5℃ / 10min, and simultaneously apply 28kHz ultrasound; in step 4:

[0106] The seed crystals have a particle size of 50-80 μm and are added at a rate of 0.3 wt%.

[0107] Final crystal Cl - Content ≤0.08% (potentiometric titration), particle size distribution span (D90-D10) / D50 ≤0.7.

[0108] Step 5: Closed-loop recycling

[0109] The leaching residue, after being mixed with 3wt% CaF2 and returned to the cement kiln, showed an activity index ≥80% after 28 days.

[0110] The crystallization mother liquor is recycled 5-8 times via nanofiltration membrane (operating pressure 2.0 MPa);

[0111] Electrolysis of exhaust gas absorbent (current density 25 mA / cm²) 2 Sodium hypochlorite with an available chlorine content of ≥5% is generated.

[0112] In step 5:

[0113] Nanofiltration membrane has an organic matter rejection rate of ≥95% (UV-Vis detection);

[0114] The current efficiency for electrolyzing sodium hypochlorite is ≥85% (calibrated by iodometric titration). Detailed implementation method:

[0116] Magnetic separation module: Bypass ash is fed into a gradient magnetic field (0.8T→1.0T→1.2T), the Fe3O4 removal rate is 91.5%, and the Fe2O3 content is reduced from 4.2wt% to 1.3wt%.

[0117] Dynamic activation module: Magnetic separation ash is mixed with 1.5 wt% NH4Cl, calcined at 600℃ for 30 min, then CO2 (2 L / min) is introduced and calcined at 400℃ for 60 min. The specific surface area of ​​the activated ash is 21.5 m². 2 / g, potassium nepheline decomposition rate 87.3%;

[0118] Countercurrent leaching module:

[0119] Primary leaching: 4 mol / L hydrochloric acid, ultrasonic treatment at 80℃ (40 kHz, 0.5 W / cm²). 3 40 minutes;

[0120] Secondary enhancement: leaching with 0.1 mol / L ammonium fluoride + 0.1 wt% sodium dodecyl sulfonate for 20 min;

[0121] Three-stage washing: After countercurrent rinsing, the total potassium recovery rate was 96.2%;

[0122] Ion sieving module: Bipolar membrane electrodialysis (20V) removes 92.5% Na. + K adsorbed by molecular sieve + Purity 99.5%;

[0123] Crystal phase control module: Concentrate to potassium concentration of 152 g / L, add 50 μm (200) crystal facet KCl seeds, and crystallize using 28 kHz ultrasonic-assisted crystallization. - Content 0.07%, D50 = 105 μm;

[0124] Recycling module: After adding 3wt% CaF2 to the leaching residue, the cement activity index is 82%, and the leaching rate remains at 90% after the mother liquor is recycled 7 times.

[0125] Indicators Conventional acid leaching method The present invention Potassium leaching rate 78% 94% K + / Na + Separation ratio 18:1 58:1 crystal Cl - content]]> 0.25% 0.07% Number of times of mother liquor reuse Not reusable 7 times

[0126] This method significantly improves the potassium leaching rate compared to the traditional acid leaching method, while reducing Cl... - The content increases the number of times the mother liquor can be reused.

[0127] The main function of the bypass ash washing and water purification module is to dissolve soluble salts and separate solids and liquids in the bypass ash. During the separation process, through the cooperation of various reactors, the soluble chlorine content in the bypass ash is removed for subsequent resource treatment and utilization. This reduces the large amount of suspended solids and calcium and magnesium ions in the bypass ash washing liquid, while also reducing its turbidity. The hardness of the treated bypass ash washing liquid is controlled below 200 mg / L and the turbidity is controlled below 5 NTU, providing an effective guarantee for the subsequent evaporation and salt separation module.

[0128] The potassium salts purified in this solution can be directly packaged and sold on the market, while the remaining bypass ash can be reused to make cement. Compared with traditional processes, the overall cost is reduced by more than 35%, providing an integrated solution of "high-efficiency potassium extraction - high-purity separation - zero-waste recycling" for solid waste in the cement industry.

[0129] After being metered, bypass ash and process water enter the pre-mixing system for stirring and mixing. Through pre-mixing, the raw ash and water are fully contacted and mixed evenly before entering the primary washing system. After solid-liquid separation in the primary washing system, the ash residue sequentially enters the secondary and tertiary washing systems. Ash residue that meets the chlorine content requirements enters the raw meal mill or clinker, while the washing liquid from the primary solid-liquid separation enters the washing liquid purification unit for treatment.

[0130] The washing liquid is pumped to the softening unit, where calcium and magnesium ion removal agent is added to the softening reactor through the calcium and magnesium ion removal agent preparation and addition system. After decalcification, the washing liquid passes through the water treatment plate and frame and neutralization treatment before entering the evaporation water supply system.

[0131] MVR evaporation can be considered. The principle of a mechanical vapor recompression (MVR) evaporator is to use a high-efficiency steam compressor to compress the secondary steam generated during evaporation, converting electrical energy into heat energy and increasing the enthalpy of the secondary steam. This increased heat energy is then pumped into the evaporation chamber for heating, thus recycling the existing heat energy of the secondary steam. This allows for the supplementation of only a very small amount of external fresh steam to maintain the system's thermal balance, achieving the purpose of evaporation and concentration through the evaporator's self-circulation.

[0132] Forced circulation evaporation crystallization systems significantly reduce the risk of pipe blockage and scaling due to potential chemical reactions that produce precipitation and crystallization. After evaporation in the forced circulation evaporator, the material reaches a supersaturated state, at which point crystals continuously begin to precipitate. To ensure effective salt output and achieve wastewater crystallization, a thermal crystallization process is employed to generate a large amount of crystals within the separator. The crystallized salt is then discharged from the bottom of the crystallization separator to a thickener. After further increasing the solid content of the solution, it is discharged into a centrifuge for centrifugation. The centrifuged crystallized salt is then discharged from the system, while the mother liquor continues to be refluxed for evaporation, with only a small amount of mother liquor being discharged.

[0133] The MVR system compresses secondary steam to increase its pressure and saturation temperature, and then sends it to the evaporator as a heat source to replace fresh steam for recycling. It also eliminates the need for a secondary steam cooling system, resulting in relatively low operating costs.

[0134] The decrease in Fe2O3 content during the removal of the Fe3O4 magnetic phase using a gradient magnetic field is due to the following reasons: Physical adsorption and entrainment: Fe3O4 is magnetic, and during adsorption and removal by the magnetic field, it may entrain some Fe2O3 particles that are tightly bound to it or physically adsorbed on its surface. When Fe3O4 is precisely removed in three stages by the gradient magnetic field, these entrained Fe2O3 particles are also removed, leading to a decrease in the overall Fe2O3 content. Crystal structure and transformation: The crystal structures of Fe3O4 and Fe2O3 are related. Under the action of the gradient magnetic field, the magnetic behavior of Fe3O4 may affect its surface or internal electronic structure, thus promoting the oxidation reaction of some Fe3O4 into Fe2O3. The newly generated Fe2O3 may be more easily removed by the separation process under the action of the magnetic field due to its particle characteristics or interaction with other substances, ultimately reducing the Fe2O3 content in the system. Although the main purpose of the process is to remove the Fe3O4 magnetic phase, the above mechanisms also reduce the Fe2O3 content, achieving better impurity removal and reducing the inhibitory effect of iron impurities on subsequent reactions.

[0135] Example 2

[0136] The difference between this embodiment and Embodiment 1 is that in step 1, the bypass ash is pretreated with microwave (300-500MHz) before magnetic separation, and the pretreatment time is 5-15 minutes.

[0137] The effects of microwave pretreatment include:

[0138] 1. Improved magnetic separation efficiency

[0139] Microwave selective heating of Fe3O4 disrupts its agglomeration structure and improves its dispersion. The Fe3O4 recovery rate increased from 78% to 94%, and the Fe2O3 residue decreased from 4.2 wt% to 1.1 wt%.

[0140] 2. Mineral activation and decomposition

[0141] Mechanism: Microwave penetrating heating promotes lattice vibrations in aluminosilicates (such as potassium nepheline), lowering the decomposition temperature. The decomposition rate of potassium nepheline increased from 85% to 92%, and the calcination temperature decreased from 600℃ to 550℃.

[0142] 3. Heavy metal solidification

[0143] Microwave-induced formation of a stable silicate glass phase from PbO and SiO2. Leachate Pb 2+ The concentration decreased from 120 ppm to 15 ppm.

[0144] 4. Energy consumption and process optimization

[0145] Microwave "volume heating" shortens calcination time and reduces heat gradient loss. Calcination time is reduced from 90 minutes to 60 minutes, and energy consumption is reduced by 25%.

[0146] 5. By-product resource utilization

[0147] Microwave-generated porous Fe3O4 magnetic adsorbent. Fe3O4 attracts Cr. 6+ Its adsorption capacity reaches 120 mg / g.

[0148] The specific data is as follows:

[0149]

[0150]

[0151] Microwave pretreatment achieves a comprehensive improvement in magnetic separation efficiency, resource recovery rate, and environmental performance through selective heating, structural reconstruction, and chemical reaction promotion, while reducing energy consumption and reagent consumption.

[0152] The above are merely embodiments of the present invention. The invention is not limited to the fields covered by these embodiments. Commonly known structures and characteristics in the solutions are not described in detail here. Those skilled in the art are aware of all common technical knowledge in the field prior to the application date or priority date, are able to access all existing technologies in that field, and have the ability to apply conventional experimental methods prior to that date. Those skilled in the art can, under the guidance of this application, improve and implement this solution in combination with their own capabilities. Some typical known structures or methods should not be obstacles for those skilled in the art to implement this application. It should be noted that those skilled in the art can make several modifications and improvements without departing from the structure of the present invention. These should also be considered within the scope of protection of the present invention, and will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. A system for extracting high-purity potassium salts using cement bypass ash, characterized in that, include: Magnetic separation module: used to separate the Fe3O4 magnetic phase in bypass ash under a gradient magnetic field of 0.8-1.2T, so that the Fe2O3 content is reduced to ≤1.5wt%. Dynamic activation module: Used for two-stage calcination with NH4Cl assistance. The first stage is calcination at 600℃ for 30 minutes, followed by calcination at 400℃ with CO2 flow for 60 minutes. The CO2 flow rate is 2L / min, ensuring that the decomposition rate of potassium nepheline is ≥85% and the resulting product has a specific surface area ≥18m². 2 / g of activated ash; Countercurrent leaching module: used to achieve hydrochloric acid-ammonium fluoride synergistic leaching through a three-stage series reactor under pH 0.5-2.5 conditions, including the first stage leaching: leaching for 40 minutes in an ultrasonic environment at 80℃ using 4 mol / L hydrochloric acid. Secondary enhancement: Add 0.1 mol / L ammonium fluoride and 0.1 wt% sodium dodecyl sulfonate, and continue leaching for 20 minutes; Three-stage washing: Rinse the leachate residue with pure water in a counter-current manner, and reuse the washing liquid for the first-stage leaching; Ion sieving module: includes a bipolar membrane electrodialysis unit and Li + Type K-LTL molecular sieve adsorption tower, selectively separates K + / Na + Up to 50:1 or higher; Crystal phase control module: Used to prepare Cl by real-time feedback of supersaturation through conductivity, combined with 28kHz pulsed ultrasound and KCl seed crystals with preferred crystal orientation. - Potassium salt crystals with a content ≤0.1%; Recycling module: used to return the leaching residue to the cement kiln after adding 3wt% CaF2, and to generate sodium hypochlorite by passing the crystallization mother liquor through a nanofiltration membrane and electrolysis of the tail gas absorption liquid.

2. The system for extracting high-purity potassium salts using cement bypass ash according to claim 1, characterized in that: The magnetic field strength of the magnetic separation module is set in three gradients: 0.8T, 1.0T, and 1.2T. XRD analysis of the calcined products of the dynamic activation module showed that the intensity of the characteristic peak of potassium nepheline at 2θ = 28.5° decreased by 82-87%, and the half-maximum width of the characteristic peak of newly formed KCl at 2θ = 31.3° was ≤0.18°.

3. The system for extracting high-purity potassium salts using cement bypass ash according to claim 1, characterized in that: The ion sieving module: The bipolar membrane electrodialysis unit simultaneously generates 0.5-1.0 mol / L NaOH solution, which is recycled for pH adjustment; The Li+ type K-LTL molecular sieve has an adsorption capacity of ≥2.5 mmol / g for Na+ and a regeneration efficiency of ≥95%.

4. The system for extracting high-purity potassium salts using cement bypass ash according to claim 1, characterized in that: The crystal phase control module: Supersaturation is calculated in real time using a conductivity-concentration calibration curve, with a control accuracy of ±5%. The amount of seed crystals added is 0.1-0.5% of the solution mass, and the crystal roundness is ≥0.

85.

5. A method for extracting high-purity potassium salts using cement bypass ash, characterized in that, Includes the following steps: Step 1: Magnetic separation-activation pretreatment: The bypass ash is placed in a gradient magnetic field of 0.8-1.2T to separate Fe3O4, and the Fe2O3 content is reduced to ≤1.5wt%. The magnetic separation ash was mixed with 1.5 wt% NH4Cl under the conditions of 30% O2 concentration and a flow rate of 5 L / min: In the first stage, the potassium nepheline was calcined at 600℃ for 30 minutes, during which potassium nepheline decomposed into KCl and Al2O3. The second stage involves calcining at 400℃ with CO2 for 60 minutes to generate surface carbonate active sites. Step 2: Three-stage countercurrent leaching First-stage leaching: Immersion in 4 mol / L hydrochloric acid at 80℃ for 40 minutes under ultrasonic conditions; Secondary enhancement: Add 0.1 mol / L ammonium fluoride and 0.1 wt% sodium dodecyl sulfonate, and continue leaching for 20 minutes; Three-stage washing: Rinse the leachate residue with pure water in a counter-current manner, and reuse the washing liquid for the first-stage leaching; Step 3: Ion-targeted purification Add 5-10 g / L sodium thiosulfate to the leachate to precipitate heavy metal ions Cu. 2+ Pb 2+ ; ≥90% Na was removed by bipolar membrane electrodialysis. + ; Using Li + Type K-LTL molecular sieve adsorbs residual Na + After adsorption, K + Purity ≥ 99.3%; Step 4: Dynamic Crystallization Control Concentrate the purified solution to a potassium ion concentration of 150±5 g / L and a supersaturation of 130% and then add KCl seed crystals. Cool down to 30℃ at a rate of 1℃ / min, start a temperature oscillation program of ±5℃ / 10min, and simultaneously apply 28kHz ultrasound. Step 5: Closed-loop recycling The leaching residue, after being mixed with 3wt% CaF2 and returned to the cement kiln, showed an activity index ≥80% after 28 days. The crystallization mother liquor is recycled 5-8 times via nanofiltration membrane; The exhaust gas absorbent is electrolyzed to generate sodium hypochlorite with an effective chlorine content of ≥5%.

6. The method for extracting high-purity potassium salts using cement bypass ash according to claim 5, characterized in that: The BET specific surface area of ​​the activated ash from step 1 reaches 18-22 m². 2 / g, potassium element solubility ≥90%; The residual K2O content in the leaching residue from step 2 is ≤0.5wt%.

7. The method for extracting high-purity potassium salts using cement bypass ash according to claim 5, characterized in that, In step 3: Na+ in bipolar membrane electrodialysis + Migration rate ≥ 0.15 mol / (m 2 ·h); The operating space velocity of the molecular sieve adsorption tower is 2-4 h⁻¹. -1 Na + Penetration capacity ≥2.2mmol / g.

8. The method for extracting high-purity potassium salts using cement bypass ash according to claim 5, characterized in that, In step 4: The seed crystals have a particle size of 50-80 μm and are added at a rate of 0.3 wt%. Final crystal Cl - Content ≤0.08%, particle size distribution span (D90-D10) / D50 ≤0.

7.

9. A method for extracting high-purity potassium salts using cement bypass ash according to claim 5, characterized in that, In step 1, the bypass ash is pretreated with microwaves before magnetic separation, and the pretreatment time is 5-15 minutes.

Citation Information

Patent Citations

  • Method for producing potassium chloride by using blast furnace dust of iron and steel enterprises

    CN103435073A

  • Method for utilizing collected dust from bypass of rotary kiln

    CN105481273A